ВИКОРИСТАННЯ МЕТОДУ УСЕРЕДНЕННЯ ДЛЯ АНАЛІЗУ ПЕРЕТВОРЮВАЧІВ ПОСТІЙНОЇ НАПРУГИ В РЕЖИМІ ПЕРЕРИВЧАСТИХ СТРУМІВ В ІНДУКТИВНИХ ЕЛЕМЕНТАХ - Руденко, Ю.В. (Інститут електродинаміки Національної академії наук України, 2020)
The fundamentals of the state-space averaging method using Lagrange's theorems for calculating dc semiconductor converters, which operate in modes of intermittent currents in inductive elements, are considered. To implement the assumption introduced in the study, it is proposed to replace the capacitor in the output circuits of the converter equivalent circuit with a source of constant emf. This makes it possible to obtain a simplified mathematical model of the converter for calculating the integral characteristics, which corresponds to a jointly defined system of algebraic equations with averaged variables. Using the developed models, the parameters of the buck, boost, and inverting converters are calculated, the analytical and graphic dependencies of the limiting values of these parameters are determined, which ensure the specified operating mode. The obtained dependencies make it possible to compare the properties of converters and select their effective parameters. Ref. 10, fig. 3.